Sustenance of endothelial cell stability in septic mice through appropriate activation of transient receptor potential vanilloid-4 - Zhu, Yi-Hua; Pei, Zhen-Ming (Cellular and Molecular Biology, 2018)
Therapeutic target transient receptor potential vanilloid-4 (TRPV-4) is frequently applied in endotoxemia research. It has been reported that HC067047, an inhibitor of TRPV-4, mitigated LPS-induced injury. However, the inhibition of TRPV-4 with HC06047 did not attenuate LPS-induced symptoms and exaggerated pathology. This study was carried with a view to unravelling the reason(s) behind these conflicting results. Different doses of the inhibitor were used in the same degree of sepsis, and their effects were determined through assays for sepsis-related physiological indicators such as endothelial injury markers, coagulation index, organ damage indicators, inflammatory factor levels, and cell apoptosis. The results showed that high or low inhibitor levels had no significant effect on sepsis-related physiological indicators. These findings suggest that proper activation of TRPV-4 in sepsis is important for maintaining normal physiological function. Thus, the degree of TRPV-4 activation should match the severity of sepsis.